(3UahI ef GfJTQ ef CNHGQ UdMGA GdbQf GdMGOj YTQs - (3CHh YHO Gddg eMeO GdUZjQ Hf eMeO Hf YHO Gddg GdjaQGfj, eMeO GdUZjQ,J (B1155 (3g` s ((3YHOGddg Hf eMeO Hf YHOGddg Hf EHQGgje Hf CMeO Hf bGSe Hf eSYhO GdTGWHj s)
(3ChdgG (B:s
(3CeG HYO , aEfi de CRd efP YbOJ jOGi ERGQi eJThbkG Edi GdJWdY Ydi CNHGQ UdMGA GdbQf GdMGOi YTQ, hSGFdG gd GQJTa CMO QVGH KZQg GdehTQ HeG jchf PjdkG dcJGH OhMI GdfGTQ aj CNHGQ Cgd GdbQf GdYGTQ s
(3BNQgG (B:s
(3ced GdcJGH HMeO Gddg JYGdi Ydi jO eDdag hfSNI dg JdejPg s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B67s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B457 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B681 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B263 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs